2019
DOI: 10.1073/pnas.1819572117
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the flux as the driving force for nonequilibrium dynamics and thermodynamics in non-Michaelis–Menten enzyme kinetics

Abstract: The driving force for active physical and biological systems is determined by both the underlying landscape and nonequilibrium curl flux. While landscape can be experimentally quantified from the histograms of the collected real-time trajectories of the observables, quantifying the experimental flux remains challenging. In this work, we studied the single-molecule enzyme dynamics of horseradish peroxidase with dihydrorhodamine 123 and hydrogen peroxide (H2O2) as substrates. Surprisingly, significant deviations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…As shown in classic double reciprocal plots ( Figure 6C and inset), the behavior was nonlinear. Recent studies 44 also showed nonlinear behavior on Lineweaver-Burk plot for horseradish peroxidase. Such results were attributed to enzyme conformational changes associated to change in the apparent rate constants.…”
Section: F I G U R E 3 Intrinsic Results Obtained From the Fit Procedmentioning
confidence: 92%
“…As shown in classic double reciprocal plots ( Figure 6C and inset), the behavior was nonlinear. Recent studies 44 also showed nonlinear behavior on Lineweaver-Burk plot for horseradish peroxidase. Such results were attributed to enzyme conformational changes associated to change in the apparent rate constants.…”
Section: F I G U R E 3 Intrinsic Results Obtained From the Fit Procedmentioning
confidence: 92%
“…1); an underlying Markovian description of the complete set of slow degrees of freedom remains appropriate. Within this framework, stochastic thermodynamics was introduced (24,35,57) and is now well validated experimentally (62)(63)(64)(65). Recent efforts have thus turned to the problem of thermodynamic inference: deducing thermodynamic quantities, such as the entropy production rate, from partial observations (19,27).…”
Section: Resultsmentioning
confidence: 99%
“…Applying thermodynamic principles to metabolic networks has resulted in the discovery of energetic constraints on metabolic fluxes (4,(121)(122)(123). New experimental and theoretical approaches have been developed to identify nonequilibrium dynamics in biological systems by quantifying the breaking of detailed balance (124)(125)(126) and irreversibility (127,128). The violation of the fluctuation-dissipation relation has also been used to quantify energy dissipation at the singlemolecular level (5).…”
Section: Open Question: What Are the Energetic Costs Of Key Cellular Processes?mentioning
confidence: 99%